"Neo-PIRO": Introducing a novel grading system for surgical infections of neonates - G Raghavendra Prasad; J V Subba Rao; Amtul Aziz; T M Rashmi (Wolters Kluwer Medknow Publications, 2017)
Introduction: Quantification of surgical sepsis was never done beyond superficial, subfascial, and deep surgical site infection (SSI). Invasive surgical sepsis with systemic manifestation has not been tried to be quantified in general and pediatric surgery in particular. Hence, this attempts to develop a novel grading system to quantify neonatal surgical infections. Materials and Methods: Predisposing factors, infection, response, and organ failure (PIRO) is being used in critical care institutions for medical sepsis; it was modified with neonate-specific surgical parameters. Authors have developed a grading of these parameters into Grade I, II, and III. Results: A blinded statistical test was performed and results were put to test. Extended Mantel-Haenszel Chi-square test validated linear relationship with grade and outcome, hospital stay, deep SSI, and organ dysfunction. Analysis of variance also showed the significant relationship of changing trends in grade and outcome. (1) Higher the grade indicated the probability of death. (2) Grade I patients had less duration of hospital stay compared to Grade II and III (P = 0.04). (3) The requirement of organ support and SSI were also more in Grade III. (4) Grade I patients had less increase in trends compared to Grade II and III (F = 4.86). Authors therefore feel Neo-PIRO seems to be the first scoring system that shows a linear relationship between scores and grade. Conclusion: Neo-PIRO is a novel grading system with surgical neonate-specific parameters. Future versions to include molecular parameters, as well as parameters selected by regression analysis.